(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract Based on Pekanbaru City Health Profile data in 2017, the coverage of pregnant women’s visits at Sidomulyo Health Center was 1.985. The results of a preliminary survey at Sidomulyo Health Center found 80% of pregnant women experienced back pain. One of the non-pharmacological methods to reduce back pain during pregnancy is pregnancy exercise. This study aimed to determine the decrease in back pain in third trimester pregnant women with pregnancy exercise. This study used a pre-experimental designconducted in Sidomulyo Community Health Center Pekanbaru from March to June 2019. The population was trimester III pregnant women who came to check their pregnancy at the Sidomulyo Health Center in March-May 2019 with a sample size of 15 taken using purposive sampling technique. Data collection was done by assessing the back pain of pregnant women before and after pregnancy exercise. The results showed that the average back pain before pregnancy exercise was 3.87, whereas after pregnancy exercise was 1.73. There was a decrease in pain intensity after pregnancy exercise (p = 0.001). It is expected that midwives should be able to conduct counseling especially in third trimester pregnant women to do pregnancy exercises